ANALISIS PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMISARIS INDEPENDEN, LEVERAGE,DAN KONSENTRASI KEPEMILIKAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze the effect of firm size, firm age, independent commissioner, leverage and concentration of ownership of intellectual capital disclosure. This analysis uses the independent variables are firm size, firm age, independent commissioner, leverage and concentration of ownership and intellectual capital disclosure dependent variable. Statistical methods using multiple linear regression analysis, the statistical test of hypothesis testing and statistical test t F. The samples used were secondary data from the Indonesia Stock Exchange (IDX) ie financial statements and Annual Report manufacturing company in 2012 listing on the Stock Exchange. Samples were taken by purposive sampling method, and who meet the criteria for sample selection. The sample used by 77 companies. The results of this study showed partial firm size variables affecting intellectual capital disclosure. Age does not affect the company intellectual capital disclosure. Independent Commissioner does not affect the disclosure of intellectual capital, leverage does not affect the disclosure of intellectual capital, and does not affect the concentration of ownership of intellectual capital disclosure. Simultaneous testing showed five variables affecting intellectual capital disclosure.Keywords: Intellectual Capital Disclosure, Firm Size, Firm Age, Independent Commissioner, Leverage and Concentration of Ownership